Prevalence of pelvic floor symptoms in female patients attending the two-week wait clinic with suspected colorectal cancer - Bennett, J (Ann R Coll Surg Engl, 2016)
INTRODUCTION: The aim of this study was to establish the prevalence of pelvic floor symptoms in women referred to a colorectal two-week wait (2WW) clinic with suspected colorectal cancer. METHODS: A questionnaire assessing faecal incontinence (FI) (Wexner score) and obstructed defecation syndrome (ODS) (Renzi score) was offered to 98 consecutive female patients attending a colorectal 2WW clinic at a single trust. RESULTS: Overall, 56 (57%) of the 98 patients had significant ODS and/or FI (scores >9/20), 33 (34%) had ODS and 40 (41%) had FI. Seventeen patients (17%) had both ODS and FI. Analysis of the 63 patients referred with a change in bowel habit (CIBH) showed 40 (63%) to be Renzi and/or Wexner positive compared with 16 (46%) of the 35 patients who presented without CIBH (p=0.095, Fisher’s exact test). Further analysis showed that 31 (78%) of the 40 patients with FI presented with CIBH compared with 32 (55%) of the 58 without FI (p=0.032). In terms of ODS, 23 (70%) of the 33 patients with ODS presented with CIBH compared with 40 (62%) of the 65 without ODS (p=0.506). CONCLUSIONS: Over half of the female patients attending our colorectal 2WW clinic had significant pelvic floor dysfunction (FI/ODS), which may account for their symptoms (especially in the CIBH referral category). While it is important for malignancy to be excluded, many patients may benefit from investigation and management of their pelvic floor dysfunction as the cause for their presenting symptoms.